Amplitudo of accommodation in the many types of myopia - Nugraha Wahyu Cahyana, Nugraha Wahyu Cahyana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: It has been discussed among ophthalmologists whether myopia is caused by environmental factors or hereditary. One of the environmental factors is the demand of work requiring frequent and close inspection with the eyes. Myopia may develop in eyes as an adaptation to reduce demands of physical type of work.Objective: To evaluate the difference of amplitudo of accommodation in many types of myopia, and the relation between amplitudo of accommodation and the degree of myopia.Methods: Subjects of the study were myopic patients in the Eye Polyclinic of Dr. Sardjito General Hospital, Yogyakarta from November 1,2000 to March 31, 2001. Subjects were divided into 4 groups: mild, moder-ate, high, and progressive myopia. Amplitudo of accommodation was examined with spherical minus method. Sex, age, family history, occupation, education level, and onset of myopia were registered, tabu-lated and analysed.Results: The subjects of the study consisted of 64 myopia patients: 16 mild myopic patients, 16 moderate myopic patients, 16 high myopic patients, and 16 progressive myopic patients. The average amplitudo o accommodation in the mild myopia group was 6.66 ± 1.28 D; the moderate myopia group was 5.03 ± 1.117 D; the high myopia group was 3.53 ± 0.59 D, and the progressive myopia was 2.89 ± 1.14 D. There was a significant difference for each group (p<0,001). There were negative significant correlations (r = -0,758) between the amplitudo of accommodation and the degree of myopia.Conclusion: There was a difference in amplitudo of accommodation for each group of myopia. There was a negative correlation between amplitudo of accommodation and the degree of myopia.Keywords : amplitudo of accommodation - degree of myopia - negative correlation - adaptation mechanism - hereditary factor